Altered frontal and transverse plane tibiofemoral kinematics and patellofemoral malalignments during downhill gait in patients with mixed knee osteoarthritis. Issue 10 (16th July 2015) - Farrokhi, Shawn; Meholic, Brad; Chuang, Wei-Neng; Gustafson, Jonathan A.; Fitzgerald, G. Kelley; Tashman, Scott
Abstract Patients with knee osteoarthritis often present with signs of mixed tibiofemoral and patellofemoral joint disease. It has been suggested that altered frontal and transverse plane knee joint mechanics play a key role in compartment-specific patterns of knee osteoarthritis, but in-vivo evidence in support of this premise remains limited. Using Dynamic Stereo X-ray techniques, the aim of this study was to compare the frontal and transverse plane tibiofemoral kinematics and patellofemoral malalignments during the loading response phase of downhill gait in three groups of older adults: patients with medial tibiofemoral compartment and coexisting patellofemoral osteoarthritis (n=11); patients with lateral tibiofemoral compartment and coexisting patellofemoral osteoarthritis (n=10); and an osteoarthritis-free control group (n=22). Patients with lateral compartment osteoarthritis walked with greater and increasing degrees of tibiofemoral abduction compared to the medial compartment osteoarthritis and the control groups who walked with increasing degrees of tibiofemoral adduction. Additionally, the medial and lateral compartment osteoarthritis groups demonstrated reduced degrees of tibiofemoral internal rotation compared to the control group. Both medial and lateral compartment osteoarthritis groups also walked with increasing degrees of lateral patella tilt and medial patella translation during the loading response phase of downhill gait. Our findings suggest that despite the differences in frontal and transverse plane tibiofemoral kinematics between patients with medial and lateral compartment osteoarthritis, the malalignments of their arthritic patellofemoral joint appears to be similar. Further research is needed to determine if these kinematic variations are relevant targets for interventions to reduce pain and disease progression in patients with mixed disease.